2018
DOI: 10.4067/s0718-07642018000300229
|View full text |Cite
|
Sign up to set email alerts
|

Campos Electromagnéticos No Ionizantes para la Inocuidad Alimentaria

Abstract: Se realizó un estudio sobre los efectos e influencia que tienen los campos electromagnéticos convencionales (Wifi y Celular) sobre microorganismos contaminantes. El estudio se realizó utilizando medios Luria-Bertani (LB) y Agua Peptonada 2,5% (WP), en dos canales de la banda Wifi (1 y 11), utilizando muestras de control en cada caso, por un periodo de 2 días a-30 dBm. Los resultados muestran un significativo descenso en la viabilidad de Escherichia coli ATCC25922 crecida en WP. Sin embargo, no se encontró camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Therefore, strategies like treatment with ozone, gaseous chlorine dioxide, high hydrostatic pressure, pulsed electric fields, short-wave UV, ultrasound, and gamma radiation are being applied and/or studied [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, the high sanitary requirements of foods and the consumers’ concern regarding the degree of intervention involved in their processing are generating a need to implement new sanitation techniques with low impact on products [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, strategies like treatment with ozone, gaseous chlorine dioxide, high hydrostatic pressure, pulsed electric fields, short-wave UV, ultrasound, and gamma radiation are being applied and/or studied [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, the high sanitary requirements of foods and the consumers’ concern regarding the degree of intervention involved in their processing are generating a need to implement new sanitation techniques with low impact on products [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Latif et al [ 23 ] showed that there are changes in the genome of E. coli and S. aureus caused by exposure to a 900 MHz EMF. Rodriguez et al [ 15 ] studied the effect of EMF on the viability of E. coli ATCC25922 in peptone water. After a 48-h exposure to a 2.412 GHz and 2.462 GHz, it was determined that there is statistically significant inhibition of the bacterial growth, with the inhibition value being greater than one logarithmic cycle.…”
Section: Introductionmentioning
confidence: 99%